Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.4319/lo.1987.32.4.0929
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scales in CZCS‐chlorophyll imagery of the southeastern U.S. continental shelf1

Abstract: A 1-yr time series of Coastal Zone Color Scanner (CZCS) imagery of continental shelf waters off the southeastern U.S. was statistically analyzed to determine dominant scale lengths in the range from 2 to 100 km for near-surface chlorophyll (Chl) variability. For each image, we extracted two-dimensional matrices of CZCS-Chl concentrations from each of 10 study areas. Variograms (structure functions) were calculated for both the along-and across-shelf dimension of each data matrix, although we designed the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 29 publications
2
51
0
Order By: Relevance
“…At the interface between oceanic and coastal processes, continental shelf regions are characterized by complex dynamics resulting from the interaction between different water masses at smaller spatial scales than the open ocean (Yoder et al, 1987). While wind, topography, or density-driven processes mostly influence the mixing and advection of the physical characteristics (temperature and salinity) of the shelf water masses, locally acting ecological processes are also determinant for biogeochemistry (Ballantyne et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At the interface between oceanic and coastal processes, continental shelf regions are characterized by complex dynamics resulting from the interaction between different water masses at smaller spatial scales than the open ocean (Yoder et al, 1987). While wind, topography, or density-driven processes mostly influence the mixing and advection of the physical characteristics (temperature and salinity) of the shelf water masses, locally acting ecological processes are also determinant for biogeochemistry (Ballantyne et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplankton biomass is assessed through several different optical proxies, including in situ chlorophyll a fluorescence (Chl F ; Lorenzen, 1966), the phytoplankton absorption coefficient (a phy (λ)) or particulate absorption coefficient in waters dominated by phytoplankton (Bricaud et al, 1995;Roesler and Barnard, 2014), and chlorophyll derived from in situ or remotely sensed ocean reflectance at visible wavelengths (O'Reilly et al, 1998). High-frequency optical measurements are ideal for detecting temporal change and spatial patchiness and for improving our understanding of the role of meso-and submesoscale physics in the distribution of phytoplankton in the ocean (Denman and Platt, 1976;Yoder et al,…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that physical and biological spatial and temporal variabilities increase with increasing proximity to shore Chang et al, 2002;Lovejoy et al, 2001;Yoder et al, 1987). This phenomenon has been referred to often in Stommel diagrams (Stommel, 1963;Lovejoy et al, 2001;Dickey, 1991) and on broad scales, has been accepted as common knowledge.…”
Section: Critical Scales Of Variability As a Function Of Distance Offmentioning
confidence: 98%
“…Considerable attention has been given to determine scales of biological and physical oceanographic processes and to identify the drivers of plankton patchiness. These questions have been addressed using a variety of different methods, including spectral analysis (Denman and Platt, 1976;Losee et al, 1989;Lovejoy et al, 2001;Washburn et al, 1998;Wiebe et al, 1996), autocorrelation or autocovariance functions (Chang et al, 2002;Mackas, 1984;Yu et al, 2002) correlograms or variograms (Dustan and Pinckney, 1989;Mackas, 1984;Yoder et al, 1987), wavelet analysis (Deutschman et al, 1993;Machu et al, 1999;Charria et al, 2003), and multifractal analysis (Seuront et al, 1996(Seuront et al, , 1999. Better understanding of the scales of variability can be used to help identify the physical and biological processes structuring biomass distribution and community structure, and help distinguish which processes are responsible at different scales (Chang et al, 2002;Cunningham et al, 2003;Dustan and Pinckney, 1989;Seliger et al, 1981).…”
Section: Introductionmentioning
confidence: 99%